2008
DOI: 10.1097/bcr.0b013e31818b9e0e
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a 12-Week Rehabilitation Program With Music & Exercise Groups on Range of Motion in Young Children With Severe Burns

Abstract: Previous studies indicate that rehabilitation programs supplemented with a strength and endurance-based exercise program improve lean body mass, pulmonary function, endurance, strength, and functional outcomes in severely burned children over the age of 7-years when compared to standard of care. To date, supplemental exercise programming for severely burned children under the age of 7-years has not yet been explored. The purpose of this study was to determine if a 12-week rehabilitation program supplemented wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 37 publications
0
32
0
Order By: Relevance
“…Neuroendocrine response to injury and immobilization may lead to muscle and bone loss. In this context, VD supplementation may be one approach among a global rehabilitation program including at least muscle reconditioning [37,38], dietary advises, treatment of sleep disorders and psychological support, and adjuvant drugs. Oxandrolone is the most studied anabolic drug in burn patients, is safe and has demonstrated beneficial effects in lean mass restoration [39,40].…”
Section: Normal Rangesmentioning
confidence: 99%
“…Neuroendocrine response to injury and immobilization may lead to muscle and bone loss. In this context, VD supplementation may be one approach among a global rehabilitation program including at least muscle reconditioning [37,38], dietary advises, treatment of sleep disorders and psychological support, and adjuvant drugs. Oxandrolone is the most studied anabolic drug in burn patients, is safe and has demonstrated beneficial effects in lean mass restoration [39,40].…”
Section: Normal Rangesmentioning
confidence: 99%
“…Only seven (17%) of the extremity contracture studies indicated the methods that were used to measure contracture. 1,2,5,10,20,21,22 Six of the seven used goniometry and one used 3D motion analysis. The six studies that used goniometry reported five different methodologies used: Norkin and White, 23 American Medical Association's "Guides to the Evaluation of Permanent Impairment," fourth edition 24 (which was adopted for the Model System for Burn Injury Rehabilitation National Database Data Dictionary), American Association of Orthopedic Surgeons guidelines, 25 and two unpublished methodologies.…”
Section: Burn Literature Review Resultsmentioning
confidence: 99%
“…Measurement of scar contracture is one such example. Measurement of scar contracture after burn injury is used by clinicians to quantify patient progress, 5 guide treatment decisions (surgical and nonsurgical), 6 and may be used to support documentation for medical reimbursement. 7 Furthermore, measurement of scar contracture is used in burn research to report incidence, 1,8,9 compare patient populations, 10 and determine outcome.…”
mentioning
confidence: 99%
“…Despite being commonly overlooked, increasing ambient temperatures reduces resting energy expenditure and attenuates the effects of the hypermetabolic response [55,56]. Exercise is important to consider in rehabilitation regimens to improve lean body mass, muscle strength and general patient outcome [66][67][68]. Non-pharmacological therapies by themselves are often times not enough to alleviate the hypermetabolic condition and pharmacological interventions are necessary.…”
Section: Discussionmentioning
confidence: 99%
“…This is further supported by studies that exercise enhances glucose control, insulin sensitivity, body composition, cardiorespiratory fitness, lipid status, and blood pressure in diabetic patients [61][62][63][64][65]. The incorporation of exercise into the regimens of convalescent burn patients is crucial, as burn patients who undergo progressive resistance exercises and aerobic exercises in addition to standard of care experience improved muscle strength and endurance, increased lean body mass, increased power, and enhanced assimilation of amino acids into muscle proteins in comparison to patients who have only received standard of care [66][67][68]. Exercise has also been shown to have synergistic effects on lean body mass and strength when coupled with specific pharmacological agents.…”
Section: Exercisementioning
confidence: 99%